The Use of Technology in Curriculum Development and Social Studies Learning Design in Elementary Schools: A Critical Analysis and Literature Review - Mustakim Mustakim; Muhamad Ajwar; I Wayan Kertih; I Wayan Lasmawan (Universitas Hamzanwadi, 2024)
This study aims to critically analyze the use of technology in curriculum development and instructional design for Social Studies (IPS) as well as Natural and Social Sciences (IPAS) in elementary schools. The method used is a literature review with a Systematic Literature Review (SLR) approach. The SLR process involves a literature search from academic databases, followed by a review of abstracts and full texts. Content analysis was employed to identify and categorize findings, while triangulation techniques were used to validate the results by comparing various sources. The study's findings indicate that technology has been integrated into the curriculum development and instructional design of IPS and IPAS in various forms, including digital platforms, interactive multimedia, online resources, and collaborative tools. This use of technology has proven effective in increasing student engagement, expanding access to learning resources, enhancing students' understanding of complex concepts, and enabling more personalized learning experiences. However, challenges in implementing technology in elementary schools remain, including infrastructure limitations, the digital divide among students, the lack of teacher skills and knowledge, as well as time and curriculum constraints. To address these challenges, the study recommends several solutions, such as intensive teacher training, improved infrastructure and technology access, and sustained support from the government and community. Continuous training can enhance teachers' skills in utilizing technology, ultimately strengthening the quality of the IPS curriculum. The study emphasizes the importance of responsive, evidence-based strategies to support the integration of technology in elementary schools.